The Teacher's Role as a Role Model: Disparities between Students' Expectations and Reality in Senior High School - Ulil Amri Syafri; Rahmatullah, Arif (TA`DIBUNA, 2025)
This research aims to analyze teacher role modeling from the perceptions of both teachers and students. This study employs mixed-methods research, combining quantitative and qualitative approaches. Research instruments included questionnaires administered to 25 teachers and 72 students as samples. The results indicate that teachers highly understand the importance of role modeling but feel less emulated by students. Conversely, students perceive teachers as good role models, despite some negative behaviors. This disparity arises from differences in perception between teachers and students, as well as the influence of social media. This disparity is analyzed through social perception theory and its relationship with the concept of social learning in Islam. Impact of this study shows that the effectiveness of role modelling is complex because it is influenced by several factors, including teacher-student interaction and the environment. Keywords: Teacher role modeling; Student perception; Disparity.